Detection of Toxoplasma gondii oocysts in environmental samples from public schools - dos Santos, Thais Rabelo [UNESP]; Nunes, Caris Maroni; Rui Luvizotto, Maria Cecilia; de Moura, Anderson Barbosa; Zanetti Lopes, Welber Daniel [UNESP]; da Costa, Alvimar Jose [UNESP]; Saraiva Bresciani, Katia Denise (Elsevier B.V., 2010)
The number of Toxoplasma gondii oocysts that can be found in random environmental samples is probably low; in addition, these cysts may be confused with Hammondia spp. and Neospora spp. oocysts. The aim of the present work was to evaluate the presence of T. gondii oocysts in the soil of public elementary schools in the northwest area of the state of São Paulo, Brazil using mouse bioassays. A comparison was made between the different available bioassay techniques, such as squash, histopathology, immunohistochemistry and indirect fluorescent antibody test (IFAT). T. gondii was isolated by bioassay in mice (squash brain samples) from 22.58%(7/31) of the school playgrounds. Immunohistochemistry and IFAT showed positive results in 32.26% (10/31) and 25.80% (8/31) of samples, respectively. The sensitivity and specificity of the immunohistochemistry method were 85.71% and 83.33%, respectively. The IFAT results showed 100% sensitivity and 95.83% specificity. The presence of T. gondii was not detected in histopathological examinations. The results of the present study strongly suggest that T. gondii oocysts are widely distributed in elementary public schools in the region that was evaluated, likely constituting the main contamination source for these children. Educational programs directed at reducing environmental contamination with T. gondii would eventually lower the cost of treating humans for clinical toxoplasmosis. It is also possible to conclude that the use of IFAT in mouse bioassays can be recommended without the need for brain cysts research, which is extremely difficult and laborious. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; Oocysts; Bioassay in mice; IFAT; Immunohistochemistry